DEVELOPMENT OF THE E-BOOK "KNOWING HISTORY AROUND US" TO INCREASE INTEREST IN LEARNING HISTORY IN ELEMENTARY SCHOOL - Anisa Rahmaniyah; Nurdinah Hanifah; Cucun Sunaengsih (Jurnal Cakrawala Pendas, 2023)
Students' interest in studying history is still low. This is caused by various factors, one of which is the monotonous learning media. This research was conducted to increase students' interest in studying history using media in the form of e-books. This research uses the R&D (Research and Development) method with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This research was conducted at SD Islam Plus Al Kayyis in Kamulyan, Bantarsari, Cilacap, with research subjects consisting of material validators, media validators, teachers or educators, and 13 grade IV students. Data collection techniques in this study used observation, questionnaires, and tests. The instruments used in this study were questionnaires given to validators, due diligence questionnaires given to teachers, and pretests and posttests given to students. Data analysis was carried out in a quantitative descriptive manner. The validation results from material experts were 82.9% in the very valid category, from media experts, 100% were in the very valid category, and the e-book 86.67% in the very feasible category. And the results of the pretest showed an average student score of 56.00 and, at the time of the posttest, showed an average student score of 91.50 which means there was an increase in learning outcomes. Media e-book is very feasible to use to increase interest in learning history for elementary school students.  Minat siswa dalam mempelajari sejarah masih rendah, hal ini disebabkan oleh berbagai faktor salah satunya media pembelajaran yang monoton. Penelitian ini dilakukan untuk meningkatkan minat belajar siswa dalam mempelajari sejarah menggunakan media berupa e-book. Penelitian ini menggunakan metode R&D (Research and Development) dengan model yang digunakan yaitu ADDIE (Analyze, Design, Development, Implementation, and Evaluation). Penelitian ini dilakukan di SD Islam Plus Al Kayyis yang berada di Kamulyan, Bantarsari, Cilacap dengan subjek penelitian yang terdiri dari validator materi, validator media, guru atau pendidik, dan siswa kelas IV yang berjumlah 13 orang. Teknik pengumpulan data dalam penelitian ini menggunakan observasi, kuesioner dan tes. Instrumen yang digunakan pada penelitian ini berupa angket yang diberikan pada validator dan angket uji kelayakan yang diberikan pada guru, dan pretest dan posttest yang diberikan pada siswa. Analisis data dilakukan secara deskriptif kuantitatif. Hasil validasi dari ahli materi 82,9% dengan kategori sangat valid, dari ahli media 100% dengan kategori sangat valid, dan hasil uji kelayakan e-book 86,67% dengan kategori sangat layak. Serta hasil pretest menunjukan nilai rata-rata siswa sebesar 56,00 dan pada saat posttest menjukan nilai rata-rata siswa sebesar 91,50 yang berarti terdapat peningkatan hasil belajar. Berdasarkan hasil yang diperoleh dapat disimpulkan bahwa media e-book ini sangat layak digunakan untuk meningkatkan minat belajar sejarah siswa sekolah dasar.